Implementasi Kebijakan Peningkatan Profesionalisme Guru SMP Negeri 3 Hu’u Kabupaten Dompu Nusa Tenggara Barat - Qurbanhajar Hajar; Budiono Budiono (Jurnal Kebijakan dan Pengembangan Pendidikan, 2020)
Abstract: This study aims to determine (1) the implementation of policies for increasing professionalism of teachers in SMP Negeri 3 Hu'u, (2) the constraints of implementing policies for increasing professionalism of teachers in SMP Negeri 3 Hu'u, (3) efforts to overcome obstacles in implementing policies for increasing professionalism teacher at Hu'u Middle School 3. This research uses a qualitative approach. The data collection techniques of this study were interviews, observation, and documentation. The results of this study indicate that (1) the implementation of the policy of increasing teacher professionalism in SMP Negeri 3 Hu'u has not been carried out to the maximum. The implementation is carried out through MGMP, PKB, Diklat, school curriculum development. Lack of opportunities to develop the profession on an ongoing basis because teachers are stuck in a routine. Teachers are also less motivated to develop professionally and personally motivated to develop their profession. (2) Constraints faced are lack of teacher sensitivity towards their profession, school policies for GTTs that do not yet have NUPTK are still not optimal, teachers delay time in various teacher development activities. (3) Efforts made in overcoming obstacles are the existence of teacher development training conducted by colleagues at the School; district-level training, workshops, teacher tutoring group learning; teacher discipline, and student discipline which must be followed by all teachers and students who are in the Hu'u 3 Public Middle School.Keywords: Policy, Professionalism, TeacherAbstrak: Penelitian ini bertujuan untuk mengetahui (1) implementasi kebijakan peningkatan profesionalisme guru di SMP Negeri 3 Hu’u, (2) kendala implementasi kebijakan peningkatan profesionalisme guru di SMP Negeri 3 Hu’u, (3) upaya mengatasi kendala implementasi kebijakan peningkatan profesionalisme guru di SMP Negeri 3 Hu’u. Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data penelitian ini yaitu wawancara, observasi, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa (1) implementasi kebijakan peningkatan profesionalisme guru di SMP Negeri 3 Hu’u belum dilaksanan dengan maksimal. Pelaksanaannya dilakukan melalui MGMP, PKB, Diklat, pengembangan kurikulum sekolah. Kurangnya kesempatan untuk mengembangkan profesi secara berkelanjutan karena guru terjebak pada rutinitas. Guru juga kurang termotivasi untuk melakukan pengembangan profesionalisme dan tergerak secara pribadi untuk mengembangkan profesinya. (2) Kendala yang dihadapi yaitu kurang adanya kepekaan guru terhadap profesinya, kebijakan sekolah untuk para GTT yang belum memiliki NUPTK masih belum maksimal, guru mengundur waktu dalam berbagai kegiatan pengembangan guru. (3) Upaya yang dilakukan dalam mengatasi kendala yaitu adanya pelatihan pengembangan guru yang dilakukan perpekan di Sekolah tersebut; pelatihan pada tingkat Kabupaten, workshop, belajar kelompok bimbingan guru; tata tertib guru serta tata tertib siswa yang harus diikuti oleh seluruh guru dan peserta didik yang berada di Sekolah SMP Negeri 3 Hu’u.Kata Kunci: Kebijakan, Profesionalisme, Guru